2012
DOI: 10.1364/oe.20.005038
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed operation of a high average power Yb:YAG thin-disk multipass amplifier

Abstract: An Yb:YAG thin-disk multipass laser amplifier system was developed operating in a 10 Hz burst operation mode with 800 µs burst duration and 100 kHz intra-burst repetition rate. Methods for the suppression of parasitic amplified spontaneous emission are presented. The average output pulse energy is up to 44.5 mJ and 820 fs compressed pulse duration. The average power of 4.45 kW during the burst is the highest reported for this type of amplifier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 20 publications
0
31
0
1
Order By: Relevance
“…However, novel laser concepts, such as thin-disk 12,13 , innoslab 14 , and fiber lasers 15 , have shown impressive advances in their performance and reached the kilowatt level of average power during pulsed operation. All of these architectures are based on ytterbium-doped laser materials that limit the attainable pulse duration to a few hundred femtoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…However, novel laser concepts, such as thin-disk 12,13 , innoslab 14 , and fiber lasers 15 , have shown impressive advances in their performance and reached the kilowatt level of average power during pulsed operation. All of these architectures are based on ytterbium-doped laser materials that limit the attainable pulse duration to a few hundred femtoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…5. It has been demonstrated that a thin-disc Yb:YAG laser can generate kW level average power with a high repetition rate in burst mode 16 and continuous mode. 17 In the earlier work by the burst mode, a multipass laser amplifier was developed to operate in a 10-Hz burst mode with 800-μs burst duration and 100-kHz intraburst repetition rate.…”
Section: Laser Assistance In Euv Fel Source Technologymentioning
confidence: 99%
“…A 15-pass amplifier was presented based on a thin-disk to amplify a 10-Hz burst of 80 pulses at 100 kHz repetition rate with 25 mJ per pulse. 104 Recent progress in large-pitch photonic crystal fibers has allowed the increase of pulse energy in fiber amplifier systems to impressive levels. CPA systems based on such fibers have been already used as OPCPA pump with up to 200 W average power resulting in the current record OPCPA average power.…”
Section: Flashlamp-pumped and Diode-pumpedmentioning
confidence: 99%